Konsep Qarīnah sebagai Alat Bukti Pembunuhan dalam Hukum Pidana Islam dan Hukum Positif Indonesia: Studi atas Kasus Jessica-Mirna - Fatkul Chodir; Muhammad Arfan Ahwadzy (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2025)
The Jessica-Mirna case shocked Indonesia due to the presence of cyanide poison in the coffee served, which became the central piece of evidence in the murder trial. Throughout the judicial process, this case sparked public debate regarding whether Jessica was justifiably convicted as the perpetrator of the crime. This study aims to examine the concept of qarīnah as indirect evidence in Islamic criminal law and Indonesian positive law through the lens of the Jessica Mirna case. Using a comparative conceptual case study approach, this research analyzes how each legal system understands, accepts, and applies qarīnah to establish the perpetrator’s intent in a premeditated murder. The findings reveal that Islamic criminal law regards qarīnah as an important indication that considers the moral aspects and intent of the accused, whereas positive law regulates qarīnah formally through stringent evidentiary procedures stipulated in the Indonesian Criminal Procedure Code. The Jessica-Mirna case demonstrates the practical application of qarīnah in the judicial process, reinforcing the role of indirect evidence in determining truth and justice. This study contributes to expanding the comparative understanding of evidentiary roles in both legal systems while strengthening the relevance of qarīnah in the modern context.